Know all about software [ types, architecture, quality, development & engineering - Osborn, Temeka (New York : College Publishing House, 2014)
The book is an attempt to give you thorough knowledge about types, architecture, quality, development & engineering of software
1. Software -- 2. Types of software -- 3. Software architecture -- 4. Software quality -- 5. Software testing -- 6. Software engineering -- 7. Software development
Keywords: Computer software; Computer software -- Development; Software engineering